Effect of noncoliforms on coliform detection in potable groundwater: improved recovery with an anaerobic membrane filter technique. - Franzblau, S G (1984)
A total of 529 well and distribution potable water samples were analyzed for total coliforms by the most-probable-number and membrane filter (MF) techniques. Standard plate count bacteria and MF noncoliform bacteria were also enumerated. Frequency of coliform detection, turbidity in most-probable-number tubes, and extensive overgrowth by noncoliforms on MF filters were directly proportional to standard plate counts. Recovery of coliforms was greatest by the MF method at low (less than 100 CFU/ml) standard plate count densities and better by the most-probable-number method (confirming gas and turbid tube) at high (greater than 500 CFU/ml) standard plate count densities. In the latter case, overgrowth by noncoliforms on MF filters suppressed sheen development and, in turn, masked coliform detection. Of 341 atypical (no sheen) MF colonies verified by parallel inoculation of lauryl sulfate broth and billiant green-bile broth, 156 were aerogenic in the latter medium. Of atypical isolates, 84% were identified as either Citrobacter or Enterobacter species. A 4.3-fold reduction in numbers of overgrown MF filters and an 2.2-fold increase in numbers of coliforms recovered from 127 water samples was accomplished by anaerobic incubation of MF cultures. This anaerobic modification of the standard MF technique significantly reduced overgrowth and enhanced recovery of coliforms from potable groundwater. This technique is simple, cost effective, and suitable for monitoring of untreated ground water common to some small water systems and private water supplies.